Diagnóstico de las asimetrías faciales y dentales (2005)
ABSTRACT: Craniofacial asymmetries are a characteristic of the human species as long as they are within reasonable limits. The asymmetries can be of dental, skeletal, functional origin or a combination of these. Likewise, there are diverse etiologic factors such as the genetic ones, the environmental ones and the functional ones that should be understood in order to achieve a good diagnosis and in this way focus on an appropriate treatment plan. The purpose of this article is to integrate the general knowledge of transversal problems focused on the diagnosis, evaluating the different etiologic factors, the prevalence and the clinical and radiographic characteristics of the dental, skeletal and functional asymmetries.